Sociodemographic, environmental and biological factors affecting uses of plants from open ecosystems: Insights for improved livelihoods and biodiversity conservation - Ahoyo, Carlos Cédric; Salako, Kolawolé Valère; Houéhanou, Thierry Dehouegnon; Montcho, Immaculée; Glèlè Kakaï, Romain Lucas; Houinato, Marcel Romuald Benjamin (Frontiers in Conservation Science, 2023)
Sustainable management of open ecosystems requires the strong participation of the neighbouring people. Attention should also be given to the species ecology which conditions the rate of vegetation growth. Socio-cultural and ecological factors contribute to both loss and conservation of fragile ecosystems. Due to the importance of traditional medicine in Benin, a focus has been made on the selection of species in this field as a case study. Further inferences highlight the conservation status of the selected woodlands and savannas. It assessed the effects of people’s sociodemographic, and species ecological parameters on the variation of the knowledge associated with their usefulness in traditional medicine in Benin. An ethnobotanical survey was conducted through semi-structured individual interviews with 590 specialists in traditional medicine. Conditional inference tree model was combined with general linear model to determine the factors associated with Traditional Medicinal Knowledge (TMK). It was found that TMK varied with informant ethnicity, source of knowledge, membership position, age, instruction level, and activity. As for the ecological and species accessibility factors, phytodistrict, mode of reproduction of the species, reasons for its disappearance, availability, and conservation status influenced the TMK. When combining the two categories of factors, phytodistrict, habitat of species conservation, source of knowledge, and membership position of the informants were highlighted as principal ones that influenced the TMK. The identified factors as important should be integrated into a comprehensive management plan for TMK conservation and biodiversity management, and then sustain the use of savanna resources. Thereby, sustainable management of open ecosystems for biodiversity conservation, livelihood improvement and climate change mitigation will be achieved. Such plan should be based on the variation of ethnicity, and the diversity of habitat of species conservation among phytodistricts.